IMPLEMENTASI KEBIJAKAN PENATAUSAHAAN BARANG/ASET NEGARA PADA BALAI PENELITIAN DAN PENGEMBANGAN PENGENDALIAN PENYAKIT BERSUMBER BINATANG DONGGALA - Vebrianto, Avib (Katalogis, 2016)
This study aims to determine the implementation of state assets/goods administration policy at Donggala Research and Development Center Animal-Sourced Diseases Control.Â  The research method used in this study was qualitative research with informants amounting to 5 (five) people. Informants were selected based on purposive sampling. This study used observation, interview, and documentation research techniques. The four dimensions studied, namely communication, resources, disposition, and bureaucratic structure, had not been going well, for the gap between the facts on the ground with the theory used and with the Government Regulation Number 27 of 2014. For the communication aspect, it was seen from the lack of the policy implementorsâ€™ understanding towards the goals. For the resources aspect, it was seen from the lack of human resources quality and quantity of the state assets/goods administrators, as well as the lack of supporting resources in the form of training budgetary for the state assets/goods administrators and from the lack of building capacity. For the disposition aspect, it was seen from the lack of a shared commitment to support the state assets/goods administration policy. For bureaucratic structures aspect, it was seen from the absence of a standard operating procedure as the guidance for the state assets/goods administrators in administrating the state assets/goods. Thus, it could be concluded that, based on the research results and discussions, the implementation of state assets/goods administration policy at Donggala Research and Development Center for Animal-Sourced Diseases Control, had not been going well.